Kesalahan Siswa dalam Menyelesaikan Asesmen Kompetensi Minimum (AKM) Numerasi SMA Topik Trigonometri - Umam, Khoirul; Chusnudhin, Rehan Muchammad Fadli; Sari, Anisa Fatwa (Jurnal Penelitian Pendidikan, 2023)
This research aims to describe students' error models in solving the Numeracy AKM test, particularly in the topic of trigonometry. This type of research is qualitative research with 3 high school students as the subjects, who are members of the IPNU IPPNU organization in Jatirejo Village, Jombang Regency. The research was conducted in the odd semester of the 2021/2022 academic year. There are three stages of analysis techniques used in this research: data collection, data reduction, and drawing conclusions. The data collection involved administering the AKM test to 6 subjects, followed by data reduction based on the three characteristics of students in solving the test. The description of the research findings is as follows: 1 student falls into the unverified solution model, 1 student falls into the misused data model, 1 student falls into the technical error model, and 2 students fall into the misinterpreted language model. Therefore, in this research, the dominant student error model is the Misinterpreted Language model, which refers to students' errors in translating the problems into mathematical language.